Strategies for preventing group B streptococcal infections in newborns: a nation-wide survey of Italian policies - Chryssoula Tzialla; Alberto Berardi; Claudio Farina; Pierangelo Clerici; Alessandro Borghesi; Elsa Viora; Paolo Scollo; Mauro Stronati; Task Force for group B streptococcal infections for the Italian Society of Neonatology; Italian Society of Obstetricians and Gynecologists; Italian Association of Clinical Microbiologists (BMC, 2017)
Abstract Background There are no Italian data regarding the strategies for preventing neonatal group B streptococcal (GBS) infection. We conducted a national survey in order to explore obstetrical, neonatal and microbiological practices for the GBS prevention. Methods Three distinct questionnaires were sent to obstetricians, neonatologists and microbiologists. Questionnaires included data on prenatal GBS screening, maternal risk factors, intrapartum antibiotic prophylaxis, microbiological information concerning specimen processing and GBS antimicrobial susceptibility. Results All respondent obstetrical units used the culture-based screening approach to identify women who should receive intrapartum antibiotic prophylaxis, and more than half of the microbiological laboratories (58%) reported using specimen processing consistent with CDC guidelines. Most neonatal units (89 out of 107, 82%) reported using protocols for preventing GBS early-onset sepsis consistent with CDC guidelines. Conclusions The screening-based strategy is largely prevalent in Italy, and most protocols for preventing GBS early-onset sepsis are consistent with CDC guidelines. However, we found discrepancies in practices among centers that may reflect the lack of Italian guidelines issued by public health organizations.